The Role of Bhabinkamtibmas in Preventing Criminal Acts of Motor Vehicle Theft in the Jurisdiction of Cianjur City Police - Alfian Syahputra, Ridho (Police Studies Review, 2024)
The current condition of the community is very dependent on daily needs, especially the economic needs that continue to run so that criminal acts of theft appear that are utilized as meeting the needs of motor vehicle theft especially. Curanmor or motor vehicle theft often occurs and many occur in almost all walks of life, so in preventing this binmas unit through bhabinkamtibmas will provide guidance and counseling to the community to prevent the occurrence of curanmor. Bhabinkamtibmas has a role to do prevention through counseling guidance. However, in the past year there has been a decrease in these cases but the case of fraud was the highest case among the other cases and in each year it was the highest case among the other cases in the Cianjur District Police Station. From the description above, the author is interested in examining the role of Bhabinkamtibmas from several problem formulations, namely the ability of Bhabinkamtibmas personnel, the implementation of counseling guidance, the methods used by Bhabinkamtibmas and infrastructure. Conceptual literature contains two research results that are relevant to this study. The theory that the writer uses in this research is based on management theory, routine activity theory, the concept of Bhabinkamtibmas, the concept of criminal theft, and the concept of criminal motor vehicle theft. The approach used by the authors in this study is a qualitative approach and the type of research is field study. The focus of the study was on the role of Bhabinkamtibmas counseling guidance in the Cianjur city police station. The sources used are primary and secondary sources. Data collection techniques used in this study were interviews, observation and document study. The author uses triangulation techniques in determining the validity of the data. Data analysis techniques used are data reduction, data presentation, and conclusions. The findings obtained by the author during the study are that not all of the Bhabinkamtibmas personnel have ever followed Dikjur. The budget to carry out the tasks in accordance with the role of Bhabinkamtibmas does not exist, the facilities and infrastructure are still inadequate so the methods used to carry out counseling guidance are not optimal because there are still very limited supporting facilities. The author's suggestion is to collaborate with the community through the village head in maintaining security and order and to hold training activities for members of the City of Bhabinkamtibmas Cianjur Sector Police in order to carry out their duties and responsibilities properly and have a basis in carrying out their daily duties.